Effects of different types of Advance Care Planning workshops: A scoping review protocol - Liu Yang; Cui Su; Xianlin Wang; Mei Chen; Renli Deng (PLoS ONE, 2025)
Introduction Advance Care Planning(ACP) plays a crucial role in ensuring that patients’ wishes are respected and fulfilled, helping to improve the quality of care and the efficient use of resources. Achieving effective ACP promotion depends on appropriate education and training. Evidence exists that ACP workshops are feasible and effective in enhancing the understanding, competence, confidence, and engagement in ACP among trainees. Systematic summary and analysis of existing ACP workshop-related research will help identify knowledge gaps and research trends in the current field and provide a standardized framework and empirical support for future training design. Objectives The overall aim of this scoping review was to systematically map existing literature about ACP workshops, provide an overview of the contents and effects of various ACP workshops, and identify limitations and gaps in knowledge. Methods This scoping review will adhere to the JBI methodology and the results will reported according to the PRISMA-ScR guidelines. Relevant articles will be systematically searched in six electronic databases (Pubmed, PsycINFO, CINAHL, Scopus, Web of Science, and Google Scholar). The research on ACP workshops conducted in any population will be included. Two reviewers individually selected the studies: first by screening titles and abstracts and second by screening full-text articles. A third reviewer will arbitrate discrepancies during the screening process. Extract data in a standardized manner using forms that have undergone team review, and data will then be synthesized and interpreted. Discussion This scoping review will identify effective training methods, topics, and research gaps by comparing the content and effectiveness of different workshops, which will help to form best practices and enhance the effectiveness of ACP training. REGISTRATION DETAILS: Open Science Framework under https://doi.org/10.17605/OSF.IO/2ZUP6.